(untitled) (INNOVATIVE ECONOMY, 2020)
Chyrak M.V., Chyrak I.M. THE INFLUENCE OF THE PRICE FACTOR ON THE UKRAINIAN EXPORT OF AGRICULTURAL PRODUCTION Purpose. The purpose of the article is the research of the influence of price factor and prices volatility at the world agricultural market on the volumes of Ukrainian agrarian exports, identification of the reserves of its cost increase and increase the effectiveness. Methodology of research. In the process of the research, general scientific methods were used, in particular: theoretical generalization methods – to study the theoretical foundations and existing concepts of pricing volatility in the global agricultural market; analysis and synthesis methods – to identify the causes of revenue decrease and to develop measures to increase the competitiveness of Ukrainian agrarian products in the world market; forecasting methods – to determine the possible global sales of grain crops. Findings. It is established that the agro industrial complex of Ukraine is more resistant to the influence of negative factors comparing to other export branches of the economy. It is found that the main reason for the decrease in the value of export income from the sale of agricultural products in recent years is the fall in world prices for grain crops. It is proved that the orientation of exporters to a limited number of items of agrarian commodity positions in conditions of high volatility of prices is unjustified. Originality. The scientific novelty is to justify the necessity of accelerated development of processing enterprises in order to increase the share of food products with higher value added in Ukrainian agrarian exports. Practical value. The results of the study will reduce the probable risks and increase the efficiency of participation of the Ukrainian agrarian sector in foreign trade activities by increasing the number of items of commodity positions in agricultural products and taking into account structural changes in the dynamics of world agricultural exports. Key words: world agricultural market; agrarian sector; export; world prices; price volatility; price trends; price equilibrium; market conditions